Right and interest collaboration platform based on block chain - ZHOU YUMEI; WANG LIXIN; YANG WEIXI; LUO FANGLI (2021)
The invention provides a right and interest collaboration information processing method based on a block chain. The method comprises the following steps: issuing a right and interest proof by an individual or a merchant, completing right and interest registration by a system, and confirming by an associated merchant when needed; the rights and interests in the system are affirmed in various types, and the management mechanism is responsible for completing scale setting; conversion of different rights and interests can be completed according to needs, and various rights and interests conversion algorithms can be adopted; rights and interests are transferred among different subjects in a point-to-point manner or through a rights and interests trading market; registering an intelligent contract in the system, and completing right and interest affirmation, right and interest conversion, right and interest transfer and the like; right and interest consumption can be in two modes of right and interest payment or ac